2003
DOI: 10.1159/000069946
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cutaneous CD30+ Large T-Cell Lymphoma in a Patient with Psoriasis Treated with Cyclosporine

Abstract: We report the case of a 61-year-old woman who developed an anaplastic CD30+ cutaneous T-cell lymphoma during oral cyclosporine (CsA) therapy for recalcitrant psoriasis. Two months after CsA discontinuation, clinical and histological resolution of the lymphoma was observed. However, 3 years later extracutaneous involvement of the lymphoma could be detected. The association between CsA administration and the occurrence of the lymphoma may be casual, but a relationship with immunosuppression may also be hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 5 publications
0
20
0
1
Order By: Relevance
“…4,5 Broadband and narrowband UVB do not appear to increase the risk of squamous cell carcinoma. 36,37 Recently, development of lymphomas after methotrexate [38][39][40] and cyclosporine, [41][42][43][44][45][46][47] and remission of lymphomas after withdrawal of these drugs [48][49][50][51] in psoriasis patients have been reported. We demonstrated that PUVA and systemic therapies do not significantly increase the risk of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Broadband and narrowband UVB do not appear to increase the risk of squamous cell carcinoma. 36,37 Recently, development of lymphomas after methotrexate [38][39][40] and cyclosporine, [41][42][43][44][45][46][47] and remission of lymphomas after withdrawal of these drugs [48][49][50][51] in psoriasis patients have been reported. We demonstrated that PUVA and systemic therapies do not significantly increase the risk of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There have been isolated case reports of the development of B-and T-cell lymphomas in psoriasis patients treated with cyclosporine. [116][117][118][119] It is important to note, however, that psoriasis causes a state of chronic overactivation of the immune system with a higher incidence of lymphoma and other malignancies than the normal population. 120,121 Cyclosporine has been shown to promote EpsteineBarr virus (EBV) transformation of human peripheral blood lymphocytes.…”
Section: Malignancy Potentialmentioning
confidence: 99%
“…These results have been substantiated in case reports that have shown CsA to be potentially associated with a variety of cancers from large T-cell lymphomas to Waldenström macroglobulinemia. [57][58][59][60][61][62][63] Mycophenolate mofetil MMF (Cellcept) was approved by the Food and Drug Administration in 1995 for prophylaxis against organ rejection in transplant patients. Once ingested, MMF undergoes ester hydrolysis to form mycophenolic acid, a weak organic acid that has been evaluated since the 1970s as a potential anti-psoriatic treatment.…”
Section: Cyclosporinementioning
confidence: 99%